Influence of the vicinal surface on the anisotropic dielectric properties of highly epitaxial Ba0.7Sr0.3TiO3 thin films. Issue 9 (13th February 2017) - Yao, Guang; Ji, Yanda; Liang, Weizheng; Gao, Min; Zheng, Shengliang; Wang, You; Li, Handong; Wang, Zhiming; Chen, Chonglin; Lin, Yuan
Abstract : Epitaxial Ba0.7 Sr0.3 TiO3 thin films were grown on vicinal LaAlO3 (001) substrates to investigate anisotropic microstructures and in-plane dielectric properties of the films under the strains induced by surface step terraces. Abstract : Epitaxial thin films of Ba0.7 Sr0.3 TiO3 (BST) were grown on the designed vicinal single-crystal LaAlO3 (001) substrates to systematically investigate the evolution of microstructures and in-plane dielectric properties of the as-grown films under the strains induced by surface step terraces. Anisotropic dielectric properties were observed, which can be attributed to different tetragonalities induced by vicinal LaAlO3 substrates with miscut orientations along the [100] and [110] directions with different miscut angles of 1.0°, 2.75° and 5.0°. A terrace geometric model with both compressive and tensile strained domains in the BST film was established, which is in good agreement with the experimental results. Our experimental studies not only shed new light on the heteroepitaxial growth mechanism, but also provide a promising platform for the design and integration of high performance device applications.